The Development of Teaching Material for Sexual Education as an Effort to Prevent LGBT, Sexual Abuse, and Free Sex For Junior High School Students - Nugroho Aji Prasetiyo; Pertiwi Perwiraningtyas (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
The rise of LGBT cases, sexual abuse, and free sex have recently threatened teenagers who are vulnerable to misinformation about sex. Increasing cases of violence is a clear proof of the lack of adolescent knowledge about sexual education that they should have obtained from the first year by their parents. Perceptions of people who still think taboo about sex education to adolescents become a cause that must be addressed to equip adolescents against the flow of globalization is increasingly transparent. One of the prevention efforts conducted is sexual education from an early age and more intensified in adolescence. The purpose of this study is the application of learning models and teaching materials of sexual education in accordance with the characteristics of adolescent learners, where at this age prone to sexual deviation. Sex education teaching materials synergize with the core competencies and basic competencies that have been set in the Curriculum 2013 for class IX SMP. The research and development model used in this research is Thiagarajan development model consisting of four stages, namely Define, Design, Develop, and Disseminate.